ʺEssence and Structure of Readiness for Innovative Methodological Activities of Vocational Education Teachersʺ - Malazonia , D. (Problems of Engineer-Pedagogical Education, 2024)
The essence and structure of readiness of pedagogical staff in vocational education institutions for innovative activities have been considered. An analysis of the components of this readiness has been conducted, and their main characteristics have been identified. The research examined the fundamental nature and framework of the preparedness of educational professionals for innovative methodological endeavors within the realm of professional training. The results of the research were presented, indicating the importance of this readiness in modern conditions, where the labor market undergoes changes, and the requirements for professionals constantly increase. Theoretical readiness was examined, involving knowledge of modern methodological approaches, pedagogical theories, and practices that contribute to effective teaching and student development. Practical readiness was also assessed, encompassing the ability of educators to develop and implement innovative teaching methods. A review of literature and existing studies on the readiness of educators for innovative methodological activities was conducted. A research methodology was developed, including the definition of concepts, assessment criteria, and tools for data collection and analysis. Information was gathered through surveys, interviews, and observations among vocational education teachers. The collected data were processed and analyzed to determine the level of readiness of educators for innovative methodological activities, and key issues and trends in this area were identified. Recommendations were formulated to enhance the readiness of educators for innovative methodological activities, including organizational and educational measures that can contribute to the development of this readiness. A report with the research results was prepared and submitted for further use and discussion in the educational community.